The corporate governance contribution as a creation of value for commercial partnerships between service providers and logistic operators - Rocha, Carlos Alberto da (2018)
This theoretical research identified the possibility that Governance factors contribute as evidence of value in the relationships of commercial partnerships between Logistic Operators and service providers. The data analysis allowed to identify three possible levels of grouping due to the variables of facilitators of proximity of partnerships that showed that it is possible to have a relationship with transparence between the client company and its suppliers. Most of these groups of suppliers were characterized by the intention to share operating profits with the client company, with little tolerance to financial risks of joint investments and a tendency to sign future supply contracts. Transparency, ethics and corporate responsibility have contributed to the consolidation of these groupings of partnerships among companies, as well as creating a mutual and evolutionary process of full confidence in such a way that Corporate Governance becomes the main value factor for this relationship.